Improving Trauma Survival In Remote Areas: A Review Of Paramedic-Led Critical Care In Traffic Accidents (The Review of Diabetic Studies, 2025)
This review explores the vital role of paramedics in managing critical traffic accident cases in remote areas, where distance, limited resources, and delayed hospital access challenge survival rates. It synthesizes evidence on pre-hospital trauma care, decision-making frameworks, transport strategies, and technological aids supporting paramedics in isolated regions. The study highlights how early interventions, advanced trauma life support, and telemedicine integration contribute to reducing mortality and morbidity. Furthermore, it identifies systemic barriers such as infrastructure gaps, environmental conditions, and communication limitations. The review concludes by proposing a strategic model to enhance paramedic efficiency, cross-agency coordination, and trauma survival outcomes in remote settings.